The Influence of Nonlinearity System of the Hydro-volume Vibration Mechanism on its Dynamic Characteristics; Material and Mechanical Engineering Technology; Vol. 3 - Moyzes [Moises] B. B. Boris Borisovich; Kuvshinov K. A. Kirill Alexandrovich; Plotnikova I. V. Inna Vasilievna; Vavilova G. V. Galina Vasilievna; Vtorushina A. N. Anna Nikolaevna (2025, 2025)
Title screen